Processo biotecnológico para obtenção dos compostos 2-feniletanol, acetato de 2-feniletil e B-cariofileno pela utilização de resíduo de goiaba - Galvão, Mércia de Sousa (2014)
The increasing demand for flavors in the world market requires new strategies for obtaining these compounds which can be produced via fermentation processes using low cost substrates such as agroindustrial residues. This turns out to be a viable process and the aroma compounds generated are classified as natural. Large volumes of waste in the form of bagasse, husks, kernels or seeds including from the processing of fruit pulp are generated and these can be used as substrates in these fermentations. Thus the main purpose of this work was to use agro-industrial residues for the production of volatile aroma compounds by fermentation processes. In this regard, we investigated the potential of the production of volatile compounds by submerged fermentation using guava, passion fruit and umbu processing waste as substrates using endophytic microorganisms isolated from guava, passion fruit and umbu as well as by using the pure cultures (Aspergillus niger, Kluyveromyces marxianus and Kluyveromyces lactis) to produce volatile compounds characteristic of fruity or floral aroma. Initially the fruit pulp and wastes from the processing of guava, passion fruit and umbu were chemically characterized (moisture, ash, fiber, proteins, lipids, sugars, titratable acidity, Aw, pH and soluble solids). Fermentation with different microorganisms in synthetic medium was performed and the fermented products analyzed for aroma note. From the results of this sensory analysis, the guava residue and the yeast Kluyveromyces lactis were selected since these constituents in the medium produced fruity and floral aromas. The volatile compounds produced were captured by two headspace techniques (SPME and Purge & Trap) and analyzed in a system of gas chromatography coupled to mass spectrometry. Sixty-two microorganisms were isolated and out of these six were selected. The fermented products were analyzed for pH, soluble solids and reducing sugars as well as to establish the kinetics of the fermentation process at every 24 hours for five days. The main aroma descriptors in the fermented products were fruity, honey, fruity green, plum, guava, banana and alcohol type notes. Forty-three volatile compounds were detected in the fermented product obtained by using the Guava residue in the medium. Among the compounds identified were: Ò {caryophyllene, 2-phenylethyl acetate, × n- humulene, bisabolene, humulene, 3-methyl butanol, bergamoteno, × n-cadinene, caryophyllene oxide and 2-phenylethanol. The production of volatile compounds was quite rapid and in most cases, this production occurred on the first day of fermentation and had achieved its maximum concentration between 24-48h of fermentation. According to the response surface method analysis, the conditions of the manufacturing process were optimized. Increased production of 2- phenylethyl acetate was achieved at concentrations varying from 25 and 35g/L of yeast extract, 40 to 60 g/L glucose. Ò-caryophyllene was obtained at concentrations varying between 120 and 140g/L of guava waste, and an agitation performed between 160 and 180 rpm. The production of 2-phenylethanol was obtained at agitation varying from 228rpm and 5g/L glucose. From these optimized conditions, scale-up of fermentation was performed in a bioreactor wherein 6 times larger concentration of 2-phenylethanol and Ò-caryophyllene compounds, and 1.5 times higher concentration of 2-phenylethyl acetate were obtained. This study reveals that guava residue can be used to produce aroma compounds of great importance for the flavor and fragrance industry, the compounds being 2-phenylethyl acetate, 2-phenylethanol and Ò -caryophyllene.